SISTEM PAKAR MENDETEKSI KERUSAKAN LAPTOP MENGGUNAKAN METODE CASE BASED REASONING DI PT. MRG MEGA BERJANGKA - Mohamad taufik hidayatullah; Mochamad Adhari Adiguna2 (CV. Multi Kreasi Media, 2022)
Laptops are technology that can help users complete work more efficiently, but one of the problems is that the problem of laptop damage is the most common case, if there are problems with the laptop, we often look for experts who understand the damage and it takes a lot of time, then it requires good knowledge to anticipate the occurrence of damage to the laptop. The purpose of this study is to implement Case Based Reasoning and Nearest Neighbor in making an expert system to identify damage to laptops, with this research it is expected that users can identify damage to laptop hardware independently. The knowledge base in case based reasoning is facts in the form of previous cases that have existed and a series of plots to examine, calculate and conclude a solution to a new problem or case. An expert system detecting laptop damage can be used as a tool to learn about laptop damage based on existing symptoms and can make it easier for users to repair damage to laptops.